Clinical communication in medicine - Brown, Jo, 1957-; Noble, Lorraine M.; Papageorgiou, Alexia; Kidd, Jane, 1957- (Chichester, West Sussex ; Ames, Iowa : John Wiley & Sons Inc., 2015)
Clinical Communication in Medicine brings together the theories, models and evidence that underpin effective healthcare communication in one accessible volume. Endorsed and developed by members of the UK Council of Clinical Communication in Undergraduate Medical Education, it traces the subject to its primary disciplinary origins, looking at how it is practised, taught and learned today, as well as considering future directions.Focusing on three key areas-the doctor-patient relationship, core components of clinical communication, and effective teaching and assessment-Clinical Communication in Medicine enhances the understanding of effective communication. It links theory to teaching, so principles and practice are clearly understood.Clinical Communication in Medicine is a new and definitive guide for professionals involved in the education of medical undergraduate students and postgraduate trainees, as well as experienced and junior clinicians, researchers, teachers, students, and policy makers.
Current teaching practice -- the skills of Information sharing and shared decision making
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Communication in medicine; Clinical medicine -- Methodology; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Alternative Medicine; MEDICAL -- Atlases; MEDICAL -- Essays; MEDICAL -- Family & General Practice; MEDICAL -- Holistic Medicine; MEDICAL -- Osteopathy; Medical; Physician-Patient Relations; Clinical Medicine -- methods; Communication; Physician's Role; Electronic books